The effect of transition period on performance parameters in elite female soccer players - Parpa, K. P.; Michaelides, M. A. (International Journal of Sports Medicine, 2020)
The purpose of this study was to examine the effect of a 4-week off-season period (transition period) on the anthropometric and performance parameters in elite female soccer players who participated in the UEFA women`s Champions league. Eighteen female players (age 23.6±4.3 years) underwent testing at the end of the competitive period and right after the transition period. An incremental cardiopulmonary testing, body composition assessment and isokinetic testing at 60 °/sec were performed on both occasions. The cardiopulmonary exercise testing revealed that VO2max (p=0.001) and time on the treadmill (p=0.000) were significantly reduced after the transition period that included a 2 times/week exercise regimen. Furthermore, the quadriceps torque production at 60 °/s was significantly reduced for both the right (p=0.013) and left quadriceps (p=0.004) following the transition period. Finally, body weight (p=0.001) and body fat (p=0.000) significantly increased after 4 weeks of significantly reduced training volume. It is concluded that the transition period negatively affected the anthropometric and performance parameters of the female players. These data maybe informative for coaches and trainers as they demonstrate that despite the efforts to keep the players physically active the performance parameters decreased significantly.